Do Goldfish Play the Violin? - "Henry, Wilson David " (Macmillan Children's Books: London, 1996)
In this third collection of tales about troublesome character Jeremy James, Jeremy doesn't have a haircut at the barber's, goes to a birthday party, falls in a river on a fishing trip, meets a battle-axe, creates chaos at the Nativity play, and hides cousin Melissa's violin in the goldfish pond.
Keywords: Children's stories-English fiction